Cultural Adaptation of Indonesian Muslim Women Students in Europe - Alexandria Cempaka Harum; Atie Rachmiatie; Ike Junita Triwardhani (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2024)
Cultural adaptability in the context of international students' intercultural communication has affected how communication works. Indonesian students, especially those who display their identity as Muslim women, have their challenges in adapting to both academic and social-cultural contexts. This study discusses the cultural adaptation of Indonesian Muslim women students to societies in Europe. All informants who are scholarship awardee students have obstacles in adapting, especially when communicating with the societies. This study aims to discover how Gudykunst’s Anxiety and Uncertainty Management theory interprets the experience phenomena around individuals in adapting to Societies in Europe through intercultural communication. The study uses a qualitative method with a phenomenological approach. Five informants in this research have gone through in-depth interviews, observation, and documentation. The results of the study show that the experiences are related to academic and social experiences adapting to the local community’s culture (cultural), adapting to individual personality (sociocultural), and adapting to interpersonal perceptions (psycho-cultural). Indonesian Muslim women students need to be familiar with the local community, open to accepting differences in society, and able to interpret the meaning of accepted in intercultural communication context.